COMPARISON OF TWO RADIOTHERAPY TECHNIQUES IN TREATMENT OF PATIENTS WITH DIAGNOSED INOPERABLE CERVICAL CANCER - Chakalaroski, Petar; Klisarova, Violeta; Kostadinova, Lenche; Dameska, Angela; Mitkov, Aleksandra Adziska; Ivanova, Olivera (Journal of Morphological Sciences, 2022)
Advanced cervical cancer is treated with radiotherapy, target therapy, chemotherapy or a combination of those. Standardized accepted treatment of inoperable cervical cancer is concurrent chemo-radiotherapy (CCRT) followed by brachytherapy. Radiotherapy techniques used are three-dimensional conformal radiotherapy (3D-CRT) and intensity modulated radiation therapy (IMRT). In this study participated 30 female patients, average age of 52 at the time of irradiation.3D-CRT plans were made, patients were treated on linear accelerator (LINAC) with 3D-CRT. IMRT plans were made additionally. Planning target volume (PTV) dose coverage was 105.36% for 3D-CRT and 105.64% for IMRT. Homogeneity index (HI) was 0.062 for 3D-CRT and 0.048 for IMRT. Conformity index (CI) for 3D-CRT was 1.93 for PTV of 2990.77 ccm. CI for IMRT  was 1.305 for PTV of 2019.83 ccm. Bladder V40 (%) for 3D-CRT averaged 96.61%, while IMRT averaged 73.11%. Rectal V50 (%) for 3D-CRT was 72.55% and for IMRT was 17.80%. Rectal V40 (%) for 3D-CRT and IMRT averaged 92.12% and 73.49% respectively. Quantitative Analysis of normal Tissue Effects in the Clinic (QUANTEC) â€“ V45 for 3D-CRT was 228.80ccm and for IMRT was 104.55ccm. Femoral heads dose for 3D-CRT was 51.50Gy for left and 51.29Gy for right. Absorbed doses for IMRT were 47.28Gy for left and 47.32Gy for right femoral head, respectively. 13 patients had grade 1 cystitis and urethritis, 2 with grade 2. 7 patients developed grade 1 diarrhea, 1 with grade 2. It can be concluded that dosimetrically IMRT is superior to 3D-CRT in patients treating cervical cancer. Keywords: cervical cancer, 3D-CRT, IMRT.